2016
DOI: 10.1002/prep.201500235
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Behavior of PBX

Abstract: 1IntroductionPolymer bonded explosives (PBXs) [1][2][3][4] have usually been considered as ap articulate composite material containing the energetic materials hexahydro-1,3,5-trinitro-1,3,5-s-triazine (RDX) embedded in av iscoelastic polymer binder. PBXs are widely used in av ariety of conventional engineering and aerospace fields. As ah ighly-filled composite material, PBX exhibits complex physical and mechanical properties that are dependent on an umber of variables, such as temperature, strain rate, grains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…The essential idea in the TTSP method is the assumption that the monitored parameter values obtained at short times and high temperatures can be used to predict parameter values at long times and low temperatures [3,29]. In its simplest form this principle means that curves of E(t) or log E(t) versus log (t) that are obtained at different temperatures are superposable by means of a horizontal shift along the log (t) axis.…”
Section: Constitutive Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential idea in the TTSP method is the assumption that the monitored parameter values obtained at short times and high temperatures can be used to predict parameter values at long times and low temperatures [3,29]. In its simplest form this principle means that curves of E(t) or log E(t) versus log (t) that are obtained at different temperatures are superposable by means of a horizontal shift along the log (t) axis.…”
Section: Constitutive Relationsmentioning
confidence: 99%
“…The diameter of the striker, incident and transmission bars is 20 mm, and the length of the incident and transmission bars is 1500 mm. In our work, the bars are made of aluminum, of which density and Young's modulus are 2.7 g/cm 3 and 73 GPa, respectively. In order to minimize the effects of friction on specimen-bar interfaces, a thin layer of high-purity petroleum jelly is applied between the specimen and the bar ends.…”
Section: Experimental Designmentioning
confidence: 99%
“…The de-bonding between the energetic crystals and the binder was the main fracture mode observed in the quasistatic experiments. 14,21,22 As the loading rate was increased, the stiffness of the PBX samples increased 14,15,19 and higher number of crystals were observed to fracture. 14,15,23 The main fracture mechanism for the energetic crystals was the trans-granular fracture caused by the tensile stress generated due to particle-particle contacts.…”
Section: 12mentioning
confidence: 99%
“…The fracture behavior of the PBX specimens has also been studied with uniaxial compression, [13][14][15][16][17][18][19] nanoindentation, 20 and Brazilian experiments [21][22][23] at various strain rates. The de-bonding between the energetic crystals and the binder was the main fracture mode observed in the quasistatic experiments.…”
Section: 12mentioning
confidence: 99%
“…Low‐strength and low‐impedance materials pose significant challenges in the design of experiments to determine dynamic stress–strain curves. In our previous work, the dynamic compressive properties of the PBX were studied using a modified split Hopkinson pressure bar (SHPB) experiment and a micromechanical model . It can be found that there are differences between uniaxial compression and tension in mechanical properties.…”
Section: Introductionmentioning
confidence: 99%